College of education student Facebook posts’ creation: morphological transformation - LIGAYA A. BATIANCILA; MARIBEL M. MORADAS; CATHERINE R. OFQUERIA; 2/0 CARL JAY DIAMANTE OIC-NW4d; GIDO, NATHANIEL G.; JOY MAE G. AMADEO (International Journal of Multidisciplinary Research and Studies, 2023)
Language is a highly elaborated signaling system. It serves various functions in communication, it is used to share ideas, convey feelings and emotions, etc. This study focused on the social media posting morphology of college students who are now enrolled in the first semester of the Academic Year 2022-2023 and who also studying at Madridejos Community College. The researchers are interested in uncovering more about how people use language in terms of its variety and lexical in one of the popular social media networking platforms that we all know as Facebook. The study employs a qualitative method based on textual analysis and qualitative explanations based on commonly posted words found on Facebook. Several words written by college students specializing in Education have been posted on social media platforms like Facebook. Clearly, the morphological pattern of words is gradually routing, owning to new, emerging words that are clearly adapted and exploited by language users. Morphological processes included non-concatenative, incorporation, and suppletion, and morphological transformations included multiple processes.